(3GdJPcQI HCMhGd GdehJi hCehQ GdBNQIs - (3GdbQWHj, CHh YHO Gddg, eMeO Hf CHj HcQ, J (B671 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdYdj GdCYdi Gdhdj GdehdiaEfj bO QCjJ Cf CcJH cJGHG hLjRG jchf JPcQI dfaSj hYedG UGdMG HYO ehJj aj PcQ GdehJ hCMhGd GdehJi hSejJg cJGH GdJPcQI HCMhGd GdehJi hCehQ GdBNQIs
(3BNQgG (B:s
(3Ke jHYK Gddg QjMG WjHI adG JOY eDefG EdG bHVJ QhMg Ke JHbi (B((3cPG(B) (3GdfGS HYO Pdc jJgGQLhf cJgGQL GdMeQ aj GdeQhL MJi jCJjge CeQ Gddg hGdSGYI hge Ydi Pdcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 322s
(3eYLe GdeDdajf(B: 3 / 52s
(3cTa GdXfhf(B: 1/ 390s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs